난류 미분탄화염 내 입자거동에 관한 연구 - 황승민(Seung Min Hwang) (Daehan hwan'gyeong gonghag hoeji, 2010)
Combustion measurements based on optical techniques have recently become of major interest as tools not only for clarifying the combustion mechanism but also for validating the computational results for the combustion fields. In this study, the particle behavior in turbulent pulverized coal flame are investigated using advanced optical diagnostics. A laboratory-scale pulverized coal combustion burner is specially fabricated as open type in order to apply various optical measurement techniques. The detailed particle behavior is performed by LDV (laser Doppler velocimetry) and SDPA (shadow Doppler particle analyzer). It is observed that the particle mean diameter increase as the distance from burner increases, and this is found to be caused by the decrease of small particles' diameter and increase of large particles' diameter. This is because of result in the char reaction and the particle swelling due to devolatilization, respectively. The size-classified streamwise velocities of pulverized coal particles in the central region of the jet show the same magnitude, whereas those in the outer region are different depending on the particle size. The results show that the velocity and size-classified diameter of the pulverized coal particles in the flame can be measured well by SDPA. 비접촉법으로 유동장이나 온도, 화학종 농도의 계측이 가능한 레이저 응용 계측기술은 연소 메카니즘의 해명뿐만 아니라 수치해석 결과의 정당성을 입증하는 수단으로 최근 주목받고 있다. 본 연구에서는 레이저 도플러 유속계와 쉐도우 도플러 입자 분석계를 이용하여 난류 미분탄 화염 내 입자거동에 대하여 관찰하였다. 버너는 여러 광학계측을 용이하게 하기 위하여 대기개방형으로 하였으며, 실험실 규모의 안정된 난류 미분탄화염이 형성 가능한 소형 모델버너를 제작 하였다. 그 결과 미분탄 입자의 평균입경은 연소과정이 진행함에 따라 증가하는 경향을 나타내었다. 이러한 원인은 다수의 소입경의 미분탄 입자가 휘발분을 방출하여 연소반응에 의해 소실되기 때문이다. 또한 화염 중심부에서 미분탄 입자의 속도장은 입경의 크기에 크게 의존하지 않지만, 화염 외주부에서의 미분탄 입자의 속도장은 입경에 크게 의존하고 있음을 알 수 있다.